Boys will be human : a get-real gut-check guide to becoming the strongest, kindest, bravest person you can be - Baldoni, Justin, 1984- (Harper, a imprint of HarperCollins Publishers, 2022)
This is a growing up guidebook for young boys. Highly designed and filled with activities, sidebars, and inspirational quotes, this book is the perfect social-emotional learning tool for parents and educators to jump-start conversations about masculinity with the boys in their lives. Have you ever noticed that there are unwritten rules that tell boys how to act, think, and feel Nobody knows where they came from, but one day, BAM! you suddenly feel these invisible forces, pushing you to follow the rules of masculinity, even if they don't make you happy. Be prepared: This book is raw and surprising. There is no subject off-limits or lies detected. Sometimes things might get a little uncomfortable, but that's an important part of getting to know and believe in yourself.